Modification of Combined Vibrated Power Assisted Liposuction with Periareolar Gland Excision in management of Gynecomastia - Qradaghi, Kurdo Akram (AL-Kindy College Medical Journal, 2018)
Background: The recognized procedures that have been used to treat gynecomastia are said to have relatively a long operative time, less patient satisfaction rate, they are merely used, in mild to moderate gynecomastia, leaves a mild bulging over the nipple areola complex, resulting in aesthetically unsatisfactory results. The more the grade of gynecomastia, the more complicated the used surgical techniques. This study evaluates the success rate of these simplest surgical technique in higher grades of gynecomastia. Objectives: to present the experiences with use of Modification of Combined Vibrated Power Assisted Liposuction with Periareolar Gland Excision in management of in different type Gynecomastia Type of the study: This is a retrospective study Methods: The study includes the use of a modification of combine vibrated power-assisted liposuction with periareolar gland excision applied for managing different types of gynecomastia. In 23 consecutive patients (46 breasts) treated between February of 2011 and March of 2016. Results: 23 patients (46 breasts) were successfully treated using this technique. Volume aspirated in both breast was 792 ml (range, 450 to 1600 ml). Using the periareolar excision technique, the mean operative time was 55 minutes (range, 45 to 90 minute). Complications were minimal (1.5 % per breasts), and no revisions were required. Conclusions: The modified Combined vibrated power assisted liposuction and the periareolartechnique have demonstrated to be a less time consuming versatileapproach, for the treatment of gynecomastia and consistently produces a smoothcontoured male breast, it is promising method to achieve good aesthetic results in gynecomastia surgerywhile resulting in an inconspicuous scar.